Practical Urological Ultrasound - Fulgham, Pat F.; Gilbert, Bruce R. (Springer International Publishing : Imprint: Humana Press, 2017)
This book on urologic ultrasound has proven to be beneficial to urologists in training and currently in practice, and is structured by organ system for the practice of urology in the outpatient/office setting. The second edition expands on current techniques and procedures, includes ultrasound images, and gives new information on the use of ultrasound for the diagnosis and management of male reproductive conditions. The updated edition also discusses ultrasound in the intraoperative setting, chapters on male reproduction, ultrasound protocols, and standards for urologic practices performing ultrasound. Bolstered with detailed illustrations and contributions from experts in the field, Practical Urologic Ultrasound, Second Edition is an authoritative and practical reference for all urologists worldwide in their mission to provide excellence in patient care.
Keywords: Medicine.; Radiology.; Urology.; elektronické knihy; electronic books